Methods and Instruments for Measuring Rock Hardness - Chen, Lian; Wang, Yuchen (International Journal of Mechanical and Electrical Engineering, 2025)
Hardness is a crucial property and indicator of materials, representing their ability to resist the penetration of hard objects into their surface. Particularly in rock mechanics, rock hardness not only serves as a measure of the difficulty in fracturing rocks but is also closely related to rock drillability (i.e., the resistance of rocks to drilling), compressive strength, drill bit selection, drilling efficiency, and rock fragmentation methods. Therefore, in the field of mechanical drilling, the accurate determination of rock hardness becomes critically important. With the advancement of science and technology, humanity has progressively deepened its understanding and research on rock hardness, leading to the invention of various instruments for measuring it. Industrial development has gradually phased out primitive measurement methods such as scratching and scoring, making rock hardness measurements increasingly accurate and steering the process onto a scientific track. This investigation, from the perspective of rock hardness, delves deeply into this significant mechanical property, examines the domestic and international background of rock hardness measurement techniques, summarizes the instruments, tools, methods, principles, and characteristics of rock hardness measurement, and offers insights into the future development prospects of rock hardness measurement.